2022
DOI: 10.52964/amja.0903
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapies for sodium azide intoxication; a case report and review of the literature

Abstract: Intoxications with sodium azide are rare and in almost all cases lethal in doses above 700 mg or 10mg/kg. We report a case of a patient who ingested 2 grams of sodium azide as a suicide attempt. Sodium azide irreversible blocks cytochrome C oxidase by inhibiting oxidative phosphorylation leading to cell death. There is currently no antidote available. Our patient was treated with a range of therapies, on site, in the emergency department and in the intensive care unit, such as sodium thiosulphate, methylene bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, to date, no cases have been reported in which methylene blue has been successfully used as an antidote. Other case reports described a variety of therapeutic supportive care interventions, including sodium thiosulfate, intralipid, gastric lavage with activated charcoal, hydroxocobalamin, dopamine, dobutamine, methylprednisolone, calcium gluconate, insulin/glucose, sodium bicarbonate, and adrenaline [ 4 , 14 , 23 , 24 ]. Despite extensive and aggressive supportive care measures such as exchange transfusion or dialysis, in addition to the above-described therapeutic strategies, all of these individuals had to be resuscitated, and all were unsuccessful [ 4 , 14 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, to date, no cases have been reported in which methylene blue has been successfully used as an antidote. Other case reports described a variety of therapeutic supportive care interventions, including sodium thiosulfate, intralipid, gastric lavage with activated charcoal, hydroxocobalamin, dopamine, dobutamine, methylprednisolone, calcium gluconate, insulin/glucose, sodium bicarbonate, and adrenaline [ 4 , 14 , 23 , 24 ]. Despite extensive and aggressive supportive care measures such as exchange transfusion or dialysis, in addition to the above-described therapeutic strategies, all of these individuals had to be resuscitated, and all were unsuccessful [ 4 , 14 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other case reports described a variety of therapeutic supportive care interventions, including sodium thiosulfate, intralipid, gastric lavage with activated charcoal, hydroxocobalamin, dopamine, dobutamine, methylprednisolone, calcium gluconate, insulin/glucose, sodium bicarbonate, and adrenaline [ 4 , 14 , 23 , 24 ]. Despite extensive and aggressive supportive care measures such as exchange transfusion or dialysis, in addition to the above-described therapeutic strategies, all of these individuals had to be resuscitated, and all were unsuccessful [ 4 , 14 , 23 , 24 ]. However, it is suggested that there might be a window of opportunity for the use of exchange transfusions or dialysis if applied before systemic effects [ 4 ] and in patients with no severe hemodynamic symptoms [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sodium azide ingestions are rare with a recent review identifying 156 cases of both accidental and intentional exposures between 2000 and 2020. 1 , 2 The substance is mostly used as a propellant in vehicular airbags but has also been used in laboratory, pharmacy, or industrial settings as a reagent probe, biocide, and chemical preservative. 1 The substance’s widespread availability (even through online retailers) and its prior use in terrorist attacks render this an important toxin for clinicians to be aware of.…”
Section: Introductionmentioning
confidence: 99%